2003
DOI: 10.1007/s00427-003-0374-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of autophagic programmed cell death of Drosophila salivary glands in vitro

Abstract: Autophagy, a form of programmed cell death (PCD) that is morphologically distinguished from apoptosis, is thought to be as prevalent as apoptosis, at least during development. In insect metamorphosis, the steroid hormone 20-hydroxyecdysone (ecdysone) activates autophagic PCD to eliminate larval structures that are no longer needed. However, in comparison with apoptosis, there are not many studies on the regulation mechanisms of autophagy. To provide a useful model for studying autophagic PCD, I established an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The induction of autophagy that anticipates salivary gland histolysis may act as part of a novel killing mechanism in these cells (Lee and Baehrecke, 2001;Myohara, 2004;Thummel, 2001) , 2004). However, in other circumstances, 'self-digestion' clearly promotes survival when apoptosis in prevented (Lum et al, 2005), and, consequently, it is important to understand how links between autophagy and cell death may instruct cell fates (Levine and Klionsky, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of autophagy that anticipates salivary gland histolysis may act as part of a novel killing mechanism in these cells (Lee and Baehrecke, 2001;Myohara, 2004;Thummel, 2001) , 2004). However, in other circumstances, 'self-digestion' clearly promotes survival when apoptosis in prevented (Lum et al, 2005), and, consequently, it is important to understand how links between autophagy and cell death may instruct cell fates (Levine and Klionsky, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with effects produced by p35, a broad-spectrum caspase inhibitor (Jiang et al, 1997;Lee and Baehrecke, 2001;Martin and Baehrecke, 2004), and with animals mutated for the apical caspase dronc (Daish et al, 2004). Because apoptotic and histolytic forms of cell death are similarly impacted by the same mutation, we conclude that common effector pathways, regulated by the apoptosome, underlie morphologically distinct forms of PCD.The induction of autophagy that anticipates salivary gland histolysis may act as part of a novel killing mechanism in these cells (Lee and Baehrecke, 2001;Myohara, 2004;Thummel, 2001) , 2004). However, in other circumstances, 'self-digestion' clearly promotes survival when apoptosis in prevented (Lum et al, 2005), and, consequently, it is important to understand how links between autophagy and cell death may instruct cell fates (Levine and Klionsky, 2004).…”
mentioning
confidence: 90%
“…Thus, it must be acknowledged that DNA fragmentation is neither universal nor necessarily predominant in the cell death process (Oberhammer et al, 1993;Lockshin and Zakeri, 1992;Zakeri et al, 1993). In addition, the action of endonucleases in the cell death of insects remains controversial, with its participation being confirmed by some authors (Gregorc and Bowen, 1996;Jochová et al, 1997;Foley and Cooley, 1998;Sheng-Hao and Nagoshi, 1999;Myohara, 2004) and denied by others (Lockshin, 1985;Bowen et al, 1993). In the review of Robertson et al (2000) regarding the nuclear events of apoptosis, the authors showed that the chromatin condensation and degradation of the DNA are controlled separately.…”
Section: Introductionmentioning
confidence: 93%
“…Several aspects of programmed cell death in larval insect salivary glands have been studied, mainly in the Lepidoptera and Diptera (Aidells et al 1971; Schin and Laufer 1973;Jurand and Pavan 1975;Beaulaton and Lockshin 1982;Levy and Bautz 1985;Armbruster et al 1986;Sehnal and Akai 1990;Jones and Bowen 1993;Bowen et al 1993Bowen et al , 1996Jochová et al 1997a, b;Dorstyn et al 1999;Lee and Baehrecke 2001;Myohara 2004). In the blow-fl y Calliphora, programmed cell death of the salivary glands does not emulate classical apoptosis because the cells are seen to vacuolate and swell rather than condense and shrink (Bowen et al 1996); additionally, there is basal fragmentation (Levy and Bautz 1985) and the nucleus does not show a distinct chromatin margination and blebbing (Bowen et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Histolysis of the silk gland during metamorphosis of Bombyx mori is carried out by autophagy, with lysosomal proteinases playing the key role in degrading cytoplasmic organelles in the autophagosomes (Lockshin et al 1998;Shiba et al 2001). However, real-time observation of autophagic programmed cell death of Drosophila salivary glands showed that the gland shrank due to cytoplasmic loss caused by blebbing (Myohara 2004).…”
Section: Introductionmentioning
confidence: 99%